1995
DOI: 10.1177/095632029500600301
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Formation of a Mononucleotide of the Anti-Influenza Agent 1,3,4-thiadiazol-2-ylcyanamide (LY217896)

Abstract: LY217896 is a substituted thiadiazole compound with anti-influenza activity in vitro and in the mouse model of infection. LY297336 is a ribosylated (N-4) derivative of LY217896. A highly polar intracellular metabolite of LY217896 was isolated by HPLC, and mass spectral analysis and treatment of the metabolite with alkaline phosphatase showed that it was a monophosphate (LY307987) derived from LY217896. The formation of LY307987 was inhibited by 43 and 63% when 10 μm of LY217896 was incubated with 100 μM of 8-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Analogues of a nucleic acid have been known to exhibit antiviral activity through intracellular metabolism to the phosphates. 1,3,4-Thiadiazol-2-ylcyanamide (LY217896), which had anti-influenza virus activity in vitro and in a mouse model of infection (8), was metabolized in BS-C-1 cells to the monophosphate form and inhibited IMPDH (1). It has been reported that ribavirin as a pseudobase could equivalently pair with both cytosine and uracil due to rotation of the carboxamide moiety and that RNA viruses, such as poliovirus and hepatitis C virus, use ribavirin triphosphate as a substrate for the viral RNA polymerase, and ribavirin incorporation was also found to be mutagenic (4,12).…”
Section: Discussionmentioning
confidence: 99%
“…Analogues of a nucleic acid have been known to exhibit antiviral activity through intracellular metabolism to the phosphates. 1,3,4-Thiadiazol-2-ylcyanamide (LY217896), which had anti-influenza virus activity in vitro and in a mouse model of infection (8), was metabolized in BS-C-1 cells to the monophosphate form and inhibited IMPDH (1). It has been reported that ribavirin as a pseudobase could equivalently pair with both cytosine and uracil due to rotation of the carboxamide moiety and that RNA viruses, such as poliovirus and hepatitis C virus, use ribavirin triphosphate as a substrate for the viral RNA polymerase, and ribavirin incorporation was also found to be mutagenic (4,12).…”
Section: Discussionmentioning
confidence: 99%
“…94 All these are cytostatic molecules mainly explored as anticancer agents. 180 The substituted thiadiazole compound LY217896 was shown to display broad anti-influenza virus activity 95 via IMPDH inhibition, 181 but proved ineffective in a placebo-controlled clinical trial. 182…”
Section: Ribavirin and Structurally Related Carboxamide Analoguesmentioning
confidence: 99%
“…Along these lines, it was shown that the antiviral activity and cytotoxicity of LY217896 were correlated with the formation of an intracellular metabolite (Colacino et al, 1993). This metabolite was subsequently characterized as a mononucleotide, mesoionic species that was able to inhibit IMPDH (Ehlhardt et al, 1993;Birch et al, 1995). Thus the reversal of the biological activity of LY217896 by guanosine could be explained by the drop in GTP pools as a result of the inhibition of IMPDH by the metabolite of LY217896.…”
Section: Inhibition Of Transcription Translation and Replicationmentioning
confidence: 99%